Sistem Informasi Persuratan Berbasis Web dan SMS Gateway - I Gusti Made Ngurah Desnanjaya; A A Gede Bagus Ariana; I Made Aditya Nugraha; I Gede Adnyana (Faculty of Computer Science, University of Jember, 2022)
The process of managing incoming and outgoing letters in government agencies is still using a manual system, recording is still using an agenda book which has several problems, such as the difficulty of administrative staff in finding old data due to the accumulation of letter data and the letter archiving process. In this study, a web-based mail archive system & SMS gateway mail archival system was created. This system can assist the process of filing letters. Testing this system using BlackBox testing. The research method uses the waterfall system development technique, consisting of several stages, namely the stages of needs analysis, system design, writing program code, conducting testing, and program implementation and maintenance. The data collection technique used is through the interview, observation, and literature study. The test results of the correspondence information system with features to manage officer data, manage incoming mail data, manage outgoing mail data, manage letter type data, manage travel letter data outside the region, and reports. This shows that the system created can function as expected.